An update of the Helicobacter pylori treatment: a Latin American Gastric Cancer, Helicobacter and Microbiota Study Group review - Otero R., William (2024)
Helicobacter pylori (H. pylori) is the primary etiological agent of gastric adenocarcinoma, which affects over 60% of the global population, with a significant prevalence in Latin America. Given its impact on the affected population, it is crucial to understand the diagnostic tools available for detecting this infection. While clarithromycin-based therapies are still widely used, the high rates of resistance to this antibiotic in the region needs the establishment of alternative, more effective treatments as the standard of care, such as bismuth-based quadruple therapy or high-dose dual therapy with amoxicillin. In cases of refractory infection, local data registries are valuable for informed decision-making.